The Case of the Sluggish Indonesian Textile and Garment Industry Viewed from the Perspective of Financial Distress - Andrean Eko Haryoko; Suhariyanto (Cita konsultindo, 2025)
The companies studied are the textile and garment industry in Indonesia due to its recent downturn, reviewing the impact of financial distress during the 2019-2023 research period. The population was 23 companies and the sample was 8 companies. The sampling technique used purposive sampling. Data were tested using the classical assumption test, multiple regression analysis, and moderated regression analysis using EViews 11. The results of this study indicate that liquidity has no effect on financial distress. Meanwhile, operational leverage has an effect on financial distress. Profitability is unable to moderate the relationship between liquidity and operational leverage on financial distress. Simultaneously, liquidity and operational leverage have a significant effect on financial distress. Based on these results, investors should be wise in making decisions, especially in investing their funds in the textile and garment industry